LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK MODELING UNTUK MENINGKATKAN MOTIVASI BERPRESTASI SISWA KELAS XI SMA MUSLIMIN RONGGA - Rina Nurdini; Maya Masyita Suherman; Riesa Rismawati Siddik (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
An individual's ability to achieve their ultimate success is inseparable from their level of achievement motivation. The role of Guidance and Counseling (BK) teachers in schools is crucial in assisting students who face obstacles in enhancing their achievement motivation. One effective service to support these students is providing group guidance using the modeling technique. High achievement motivation is characterized by embracing challenges, accepting failure, focusing on personal strengths, and demonstrating good time management. This study aims to help students improve their personal skills in all activities by using standards of excellence as a benchmark, while also serving as an internal driving force to attain success. The method employed is qualitative, utilizing research instruments such as interviews, observations, and documentation. The results of this study can serve as a reference in delivering group guidance services with modeling techniques to foster students' achievement motivation.